Sedimentation in Expedition Fiord, Axel Heiberg Island, Northwest Territories - Gilbert, Robert (Géographie physique et Quaternaire, 1990)
ABSTRACTExpedition River which drains 1079 km2 of glaciated landscape on eastern Axel Heiberg Island is advancing 8.7 m/a (averaged since 1959) into Expedition Fiord. This rate is the highest reported in the Canadian Arctic. Bed material is deposited in the fiord by sediment gravity flows down the foreset beds of the delta. Fresh water forms a well-defined overflow on the sea which is not significantly mixed at least 15 km from the river. However, fine-grained suspended sediment (maximum measured concentration 2.24 g/L) flocculates and settles from suspension soon after entering the fiord. As a result, the sea floor near the delta is thickly mantled with rapidly accumulating deposits of very underconsolidated. fine-grained sediment. Beyond 3 km from the delta modern sediment is restricted to a thin cover with isolated pockets of thicker accumulation in depressions.